Urban Aboriginal Creation Stories and History: contesting the past and the present. The Eleventh Doireann MacDermott Lecture - Kristina, Everett (Universitat de Barcelona, 2018)
This paper is based on the 11th annual Doireann MacDermott public lecture presented at the Universitat de Barcelona in November, 2010. It is a critique of discourses and representations in Australian society, and indeed, embedded in all western societies (and many non-western societies I suspect) which support and reinforce artificial binary oppositions which make up social structures and institutions. Binary oppositions reinforce oppositional power dynamics, making one term positive and the other negative, not recognizing categories in-between. Linguistically, for example, the terms ‘Indigenous’ and ‘non-Indigenous’ articulate a false dichotomy between people who, empirically, are not two discrete groups, but rather, multiple groups within each category which interact within and between groups in complex and fluid engagements. The discourses and representations I discuss in this paper articulate imaginary binary oppositions out of social processes and identities which are, in fact, very similar. However, because these discourses and representations are constructed by different social groups with unequal power relationships they are treated as opposites, one with a higher value than the other. In this paper I am primarily concerned with history and myth, and in two related ‘stories’, the Lachlan Macquarie story, classified as history because it is primarily written and ‘belongs’ to the dominant Australian society, and the Maria Locke story, classified as myth because it is primarily oral, and explains the emergence and characteristics of a group of Aboriginal people who claim traditional Aboriginal ownership of a large part of what is today called Sydney.